2015
DOI: 10.1111/ped.12732
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preterm birth on growth and cardiovascular disease risk at school age

Abstract: Background. Low birth weight is associated with increased risk for cardiovascular disease

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…We had a female predominance with a sex ratio of 0.75. This prevalence was comparable, in different proportions, to the findings of the other authors, 10,[12][13][14][15][16] who also found high blood pressure in premature infants compared to fullterm controls. Bonamy et al, 17 in 2017 in Switzerland, found that in children aged 6 years born before the 27th week of amenorrhoea, the blood pressure measured did not differ in the two groups.…”
Section: Hypertension In Former Premature Infants Cumulative Incidencesupporting
confidence: 88%
See 1 more Smart Citation
“…We had a female predominance with a sex ratio of 0.75. This prevalence was comparable, in different proportions, to the findings of the other authors, 10,[12][13][14][15][16] who also found high blood pressure in premature infants compared to fullterm controls. Bonamy et al, 17 in 2017 in Switzerland, found that in children aged 6 years born before the 27th week of amenorrhoea, the blood pressure measured did not differ in the two groups.…”
Section: Hypertension In Former Premature Infants Cumulative Incidencesupporting
confidence: 88%
“…17 While Namraka Vashishta found that low birth weight and young age at follow-up were associated with an increased risk of having a systolic or diastolic BP above the 90 th percentile. 12 Satomi inomata et al, 15 in 2015 in Japan, found that gestational age was positively associated with height and inversely associated with blood pressure at school age (p=0.04). 15 Grancher et al in 2014 in France found primiparityandthebirthheadcircumferencebelowthe10 th percentile significantly associated with abnormal blood pressure.…”
Section: The Associated Factorsmentioning
confidence: 96%
“…Contradictorily with previous reports, BW was not significantly associated with impaired glucose tolerance, triglyceride or high-density lipoprotein-cholesterol (HDL-C) levels, or HTN in Korean adolescents, which might imply that BW may be a limited contributing factor to the metabolic syndrome in adolescents born as SGA. A series of Japanese studies on low BW and increased CV risks found that preterm SGA children were significantly shorter and inversely associated with systolic BP at school age but did not have unfavorable lipid levels at the age of 9–10 years 54)…”
Section: Impact Of Weight Gain and Timing Of Catch-up Growth For Chilmentioning
confidence: 99%
“…), primary school age children (Inomata et al . ) and adults (Irving et al . ; Sipola‐Leppänen et al .…”
Section: Introductionmentioning
confidence: 99%
“…Ex-preterm adults have an increased risk of cardiovascular disease (Crump et al 2011;Lewandowski et al 2015). Impaired cardiovascular function following preterm birth has been demonstrated in newborns (Fyfe et al 2015), primary school age children (Inomata et al 2015) and adults (Irving et al 2000;Sipola-Leppänen et al 2015). Baroreflex control in preterm infants is inversely proportional to gestational age at birth (Gournay et al 2002), and evidence shows that maturation occurs more slowly in this population, such that at term equivalence the preterm infants still have a deficit in their baroreflex control (Andriessen et al 2005).…”
Section: Introductionmentioning
confidence: 99%